Дослідження хромвмісних реагентів в технологічних рідинах - Кустурова, Олена Валеріївна; Жуган, Оскар Анатолійович; Печеніжська, Аліна Вікторівна; Подольян, Олена Антонівна; Моцарь, Дмитро Володимирович (НТУ "ХПІ", 2017)
Розглянуто процеси інгібування диспергування глин, які впливають на продуктивність свердловин, в яких відбуваються фізико-хімічні процеси при технологічних операціях (буріння, закінчення, інтенсифікація, консервація та глушіння свердловин). Всесвітня практика встановила високі вимоги до технологічних рідин для зменшення негативного впливу на продуктивні властивості пластів. Спорудження та експлуатація свердловин в Україні відбувається не тільки в складних гірничо-геологічних умовах, але і в часи складної економічної кризи. Дані умови сприяють розвитку науково-дослідних робіт для мінімізації витрат на приготування технологічних рідин на основі вітчизняної сировини. Технологічні рідини на основі синергетичних сумішей для буріння та глушіння свердловин не повинні забруднювати продуктивні горизонти. Основа рідин буріння та глушіння є важливою для створення рецептур розчинів у складних гірничо-геологічних умовах. Особливу увагу слід приділяти густині розчинів для глушіння, щоб не допустити гідророзрив пласта.

Considered dispersion clay processes affecting the productivity of the wells. In the wells are going physical and chemical processes during technological operations (drilling, completion, stimulation, preservation and killing of wells). World practice makes high demands on technological liquids to reduce the negative impact on the productive layers. The construction and operation of wells in the Ukraine is not only in the difficult geological conditions, but also during the difficult economic situation. This situation contributes to the development of scientific research to minimize the costs for preparation of technological fluids on the basis of domestic agents. Process fluid based on synergistic mixes for conducting a well killing should not contaminate reservoirs. Fluids base for kill well are impotent for design it in difficult geological environment. During all well kills and drilling fluids, careful attention must be paid to not exceeding the formation strength at the weakest point of the wellbore, the "fracture pressure", otherwise fluid will be lost from the wellbore to the formation. We must pay attention carefully of weight fluids for drilling and kill well that it doesn’t run into productive layer. Technological fluid systems are designed and formulated to perform efficiently under expected wellbore conditions. There are many different types of technological fluids, based on different composition and use.
Research of additives based of chrome in technologicalt fluids
Keywords: пласт; корозія; синергізм; фільтрація; хром; глушіння; reservoir; corrosion; synergy; filtration; chrome; kill well